(untitled) (Al-Aasar, 2025)
Muhammad Nawaz Tair holds a distinguished position in the realm of Pashto literature, dedicating over fifty years to its promotion and development. His contributions span multiple areas, including creation, research, critique, compilation, and translation of Pashto works. Notably, Tair’s influence extends to the preservation and advancement of Pashto folklore, an area in which he has made significant strides. He has not only safeguarded ancient folk traditions but has also embedded them into his own poetry and prose, enriching the cultural fabric of Pashto literature. Through his efforts, he has attracted and inspired other writers to explore and engage with Pashto folklore. This article highlights Tair’s invaluable services to Pashto folklore and examines his role in preserving, describing, and fostering the continued growth of this integral aspect of Pashto heritage.